2000
DOI: 10.1111/j.1475-4959.2000.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of population and forest trends

Abstract: The relationship between national trends in forest area and population is reviewed at the global scale. Evidence of an inverse relationship is confirmed. The relationship, however, may have weakened in recent decades, and it has clearly undergone a reversal in some countries during the nineteenth to twentieth centuries. The theme of a changing relationship through time is thus developed, as is that of an asymmetrical relationship in the sense that the forest area is likely to stabilize before population. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(106 citation statements)
references
References 26 publications
8
86
0
12
Order By: Relevance
“…HYDE did not distribute land use in the Alpine region likely for the same reasons as in KK10 and also because HYDE concentrates land use in areas with low slope. However, severe deforestation is documented to have occurred in the Alps in the late preindustrial era (e.g., [68,69]). Crises such as floods and erosion occurring just prior to industrialization in France and Switzerland prompted legislation protecting montane forests and encouraging reforestation in the late 19th century [68,70].…”
Section: Discussionmentioning
confidence: 99%
“…HYDE did not distribute land use in the Alpine region likely for the same reasons as in KK10 and also because HYDE concentrates land use in areas with low slope. However, severe deforestation is documented to have occurred in the Alps in the late preindustrial era (e.g., [68,69]). Crises such as floods and erosion occurring just prior to industrialization in France and Switzerland prompted legislation protecting montane forests and encouraging reforestation in the late 19th century [68,70].…”
Section: Discussionmentioning
confidence: 99%
“…Soil erosion, land degradation, destruction of habitat and biodiversity; loss of endemic species due to you to out migration are resulted from land use dynamics (Meyer and Turner 1992). Even though many controversies on the factors of land cover dynamics, few research studies concluded that demographic factor is intensively accelerate to land use cover change (Mather and Needle 2000). Alarming rate of population dynamics, insecure land use right, lack of credit facilities and lack of market availability are some of socio-economic factors which facilitates for the change of land cover.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, poverty may conceal more important and complex social, political and infrastructural changes in rural populations . The apparent effect of annual population growth on conversion to agriculture may indicate a strong link between growth, poverty, population density and deforestation (Mather and Needle, 2000;Lambin et al, 2001). Our results also show that neither distance to a main highway or major city, nor road density or urban population size influenced conversion of habitats to agriculture.…”
Section: Conversion Of Land To Agriculturementioning
confidence: 53%